Puffball spores improve wound healing in a diabetic rat model - He, Tangtang; Sun, Pengfei; Liu, Bo; Wan, Shiwei; Fang, Penghua; Chen, Jun; Huang, Guicheng; Min, Wen (Frontiers in Endocrinology, 2022)
Persistent chronic oxidative stress is a primary pathogenic characteristics of diabetic foot ulcers. Puffball spores are a traditional Chinese medicine used to treat diabetic foot ulcers infections and bedsores. However, their effects against diabetic wounds and the mechanism underlying these effects remain largely unknown. The present study explored the effectiveness of puffball spores in diabetic wound treatment and the mechanisms underlying their effects. Sprague-Dawley rats with streptozotocin (STZ)-induced diabetes were treated with puffball spores to ascertain whether they accelerated wound healing.Real-time quantitative PCR, western blotting, hematoxylin-eosin and Masson’s trichrome staining, immunohistochemistry analysis, and immunofluorescence assays were performed. As indicated by wound and serum histology and biochemical analyses, the puffball spores accelerated wound healing by activating Akt/Nrf2 signaling and promoting the expression of its downstream antioxidant genes, markedly stimulating antioxidant activity and enhanceing angiogenesis and collagen deposition. Our findings showed that puffball spores could accelerate diabetic wound healing, enhance antioxidant ability, promote the expression of vascular markers, and suppress inflammation, thus providing a theoretical basis for the treatment of diabetic and refractory wounds.